Ameloblastoma uniquístico: reporte de caso en una niña de 9 años (2022)
Unicystic ameloblastoma is a benign odontogenic tumor, which accounts for less than a third of all ameloblastomas, is commonly found in the jaw, is less aggressive than other types of ameloblastoma, and occurs unusually in children. A case of unicystic ameloblastoma is reported in a 9-year-old girl, located in the anterior region of the mandible and large, the characteristics of the pathology, conservative surgical treatment and postsurgical controls are described.